2014
DOI: 10.1038/bjc.2014.265
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of basal cell carcinoma in the United Kingdom: incidence, lifestyle factors, and comorbidities

Abstract: Background:Little is known about the epidemiology of basal cell carcinoma (BCC).Methods:Using the Clinical Practice Research Datalink, we calculated annual incidence rates. In a case–control analysis, we examined lifestyle factors and comorbidities.Results:Incidence rose significantly between 2000 and 2011. Basal cell carcinoma risk was increased in alcohol drinkers (slightly) and immunocompromised patients, but reduced in smokers and individuals with abnormal weight.Conclusions:Basal cell carcinoma places a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 28 publications
3
59
0
3
Order By: Relevance
“…As a result, many were limited by broad definitions of alcohol intake (such as ‘drinker’ vs. ‘nondrinker’) and were rated as lower quality by our assessment criteria. Only one large case–control study by Reinau et al . (57 121 BCC cases) found that current alcohol drinkers had a significant but modest increase in BCC risk compared with nondrinkers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, many were limited by broad definitions of alcohol intake (such as ‘drinker’ vs. ‘nondrinker’) and were rated as lower quality by our assessment criteria. Only one large case–control study by Reinau et al . (57 121 BCC cases) found that current alcohol drinkers had a significant but modest increase in BCC risk compared with nondrinkers.…”
Section: Discussionmentioning
confidence: 99%
“…One meta‐analysis found no association between alcohol consumption and risk of BCC . Since then, recent studies have reported a positive association for BCC, cSCC and NMSC . This systematic review and meta‐analysis quantifies the association between alcohol intake and NMSC risk.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Basal cell carcinoma (BCC) is the most common type of malignancy in humans and the most common skin cancer in the elderly [84]. Although itch has not often been mentioned as a common symptom, a recent large study found that 32 % of patients with BCC had itch.…”
Section: Cutaneous Conditionsmentioning
confidence: 99%
“…14 In the United States, age-adjusted BCC incidence rates have doubled over the past 2 decades, with recent estimates of 1019 cases per 100000 person-years for women and 1488 cases per 100000 person-years for men. 5 Although it rarely metastasizes, BCC can cause significant local tissue destruction and cosmetic impairment, making treatment options challenging in advanced stages.…”
mentioning
confidence: 99%